Vibration performance assessment of deteriorating footbridges: A study of Tunja's public footbridges. (1st April 2022) - Rodríguez-Suesca, A.E.; Gutiérrez-Junco, O.J.; Hernández-Montes, E.
Highlights: Experimental campaign about vibration in eight deteriorating footbridges. New proposal of normalised single-footstep force functions for walking and running. Vibration discomfort and deterioration were compared by using VDI and DI indices. Abstract: This paper presents the results of the assessment of the dynamic characteristics and vibration performance of eight deteriorating footbridges. The bridges examined, part of the public infrastructure of the city of Tunja (Colombia), present an evident state of deterioration, showing excessive vibration under service loadings. A consistent evaluation methodology based on vibration tests and numerical analyses was implemented. After completing a deterioration assessment, an experimental modal characterization was carried out, the results of which were used to update numerical structural models. Uniform vibration tests for different pedestrian loading scenarios were conducted. Then, pedestrian crossing simulations for a typical range of walking and running frequencies were performed using a step-by-step load model with a new proposal of normalised single-footstep force functions. Results showed elevated vibrations in most of the footbridges for temporary and exceptional loading conditions, which are unsafe for some of the structures. Discomfort and deterioration were compared using a vibration discomfort index ( VDI ) and a deterioration index ( DI ). High vibration discomfort levels were found to be consistent with the degree of deterioration of the structures evaluated.